Emotion in motion: Facial dynamics affect infants' neural processing of emotions. Issue 6 (29th April 2019) - Quadrelli, Ermanno; Conte, Stefania; Macchi Cassia, Viola; Turati, Chiara
Abstract: Research investigating the early development of emotional processing has focused mainly on infants' perception of static facial emotional expressions, likely restricting the amount and type of information available to infants. In particular, the question of whether dynamic information in emotional facial expressions modulates infants' neural responses has been rarely investigated. The present study aimed to fill this gap by recording 7‐month‐olds' event‐related potentials to static (Study 1) and dynamic (Study 2) happy, angry, and neutral faces. In Study 1, happy faces evoked a faster right‐lateralized negative central (Nc) component compared to angry faces. In Study 2, both happy and angry faces elicited a larger right‐lateralized Nc compared to neutral faces. Irrespective of stimulus dynamicity, a larger P400 to angry faces was associated with higher scores on the Negative Affect temperamental dimension. Overall, results suggest that 7‐month‐olds are sensitive to facial dynamics, which might play a role in shaping the neural processing of facial emotional expressions. Results also suggest that the amount of attentional resources infants allocate to angry expressions is associated to their temperamental traits. These findings represent a promising avenue for future studies exploring the neurobiological processes involved in perceiving emotional expressions using dynamic stimuli.